High-Precision Protein-Tracking With Interferometric Scattering Microscopy - Taylor, Richard W.; Holler, Cornelia; Mahmoodabadi, Reza Gholami; Küppers, Michelle; Dastjerdi, Houman Mirzaalian; Zaburdaev, Vasily; Schambony, Alexandra; Sandoghdar, Vahid (Frontiers in Cell and Developmental Biology, 2020)
The mobility of proteins and lipids within the cell, sculpted oftentimes by the organisation of the membrane, reveals a great wealth of information on the function and interaction of these molecules as well as the membrane itself. Single particle tracking has proven to be a vital tool to study the mobility of individual molecules and unravel details of their behaviour. Interferometric scattering (iSCAT) microscopy is an emerging technique well suited for visualising the diffusion of gold nanoparticle-labelled membrane proteins to a spatial and temporal resolution beyond the means of traditional fluorescent labels. We discuss the applicability of interferometric single particle tracking (iSPT) microscopy to investigate the minutia in the motion of a protein through measurements visualising the mobility of the epidermal growth factor receptor in various biological scenarios on the live cell.